8. Low-Intensity Pulsed Ultrasound (LIPUS) Treatment for the Patient With Bone Reconstruction by the Masquelet Technique Using RIA. Issue 8 (August 2016) - Niikura, Takahiro; Yang Lee, Sang; Iwakura, Takashi; Kurosaka, Masahiro
Abstract : Background: The Masquelet technique is a relatively new option in the management of bone defects. It consists of 2-stage surgery. At first surgery, a cement spacer is placed to fill the bone defect. After a waiting period of 6–8 weeks, a pseudo-synovial membrane is formed around the cement. The induced membrane is rich in vascularity and osteogenic activity. At second surgery, the cement is replaced with an autologous bone graft and the graft is packed in the membrane. To harvest large quantities of bone graft, the reamer irrigator aspirator (RIA) is utilized. We report a case in which low-intensity pulsed ultrasound (LIPUS) was applied to bone reconstruction by the Masquelet technique using RIA. Case: The patient was a 44-year-old man. He suffered a tibia fracture involving the proximal part and the shaft. Open reduction and internal fixation was performed at the previous hospital. However, MRSE infection was found at 6 months postoperatively and surgery to eradicate the infection was performed. Two months after surgery, pseudoarthrosis surgery was performed; however no progression in bone union was observed for 5 months. Therefore, the patient was referred to our hospital. At the first surgery in our hospital, plates and screws were removed, and the avascular bone was debrided. Vancomycin-impregnated cement was placed to fill the bone defect and an Ilizarov external fixator was applied. Eight weeks later, the cement was replaced with the autologous bone graft and the graft was packed in the induced membrane. Bone graft was harvested from the ipsilateral femur using RIA. We applied LIPUS to the affected site postoperatively. Now, 4 months after the second surgery, bone union is progressing and the patient can walk without pain. Discussion: LIPUS may be used as an adjuvant therapy for a patient treated by the Masquelet technique using RIA.